Effects of boiling and steaming process on dietary fiber components and in vitro fermentation characteristics of 9 kinds of whole grains. (February 2023) - Fang, Fang; He, Yuxin; Zhao, Jutang; Zhang, Yanli; Chen, Chunhua; He, Huijun; Wu, Quanyong; Hu, Mengwei; Nie, Shaoping; Xie, Mingyong; Hu, Jielun
Graphical abstract: Highlights: Dietary fiber contents in boiled, steamed and unprocessed whole grains were evaluated. In vitro fermentation characteristics of boiled and steamed grains were compared. Effects of processed grains on fecal microbiota during fermentation were analyzed. Abstract: Whole grains (WGs) are considered as the representative sources of dietary fiber (DF). Thermal treatments can change the properties of DF, and potentially affecting the gut microbiota as well as human health. In this study, DF content and in vitro fermentation characteristics of 9 kinds of WGs (highland barley, barley, buckwheat, proso millet, quinoa, sorghum, coix seed, foxtail millet, and oats) after boiling and steaming treatments were compared. It was found that boiling and steaming treatments could both increase DF content in these grains, except for barley and foxtail millet. Processed WGs could regulate beneficial microbial genus, such as Bifidobacterium, Prevotella, Megamona and Megasphaera. Oats, quinoa, highland barley, and buckwheat after boiling treatment can produce more total short-chain fatty acids (SCFAs) than steaming treatment ( p < 0.05), while barley, foxtail millet and coix seed showed opposite results. This study can provide data support for the design of WGs diets and the development of WGs products which are beneficial for gut health.